99mTc-labeled benzenesulfonamide derivative-entrapped gold citrate nanoparticles as an auspicious tumour targeting - Adli A. Selim; Tamer M. Sakr; Basma M. Essa; Galal H. Sayed; Kurls E. Anwer (Scientific Reports)
Abstract Sulfonamide derivatives are a significant class of medicinal compounds. Gold nanoparticles (AuNPs) offer precise cancer treatment through targeted delivery, boasting high drug-loading capacity and low toxicity. This study aimed to develop and evaluate 99mTc-labeled benzenesulfonamide derivative-entrapped gold citrate nanoparticles as a tumor-targeting agent. A novel benzenesulfonamide derivative bearing a pyridine moiety was synthesized. Compound 3 (4-((3-cyano-4-(2,4-dichlorophenyl)-6-phenylpyridin-2-yl)amino)-N-(diaminomethylene)benzenesulfonamide) exhibited remarkable anti-cancer activity against MCF-7 cells. The chemical reduction method was employed to create compound 3-citrate-AuNPs. A comprehensive examination of the synthesized nano-platform was conducted, including zeta potential, size analysis, radiochemical yield, and in-vivo biodistribution in tumor-bearing mice. The nano-platform was successfully produced with good stability, optimal particle size (9 nm diameter for AuNPs), and high radiochemical purity for [99mTc]Tc-compound 3 (88.31 ± 2.14%). In-vivo investigations revealed that intravenously administered [99mTc]Tc-compound 3-citrate-AuNPs accumulated in tumors with a high target-to-non-target ratio. The findings validate the efficacy of the novel [99mTc]Tc-compound 3-citrate-AuNPs platform as a tumor-targeting agent.